Development of a tomato xylem-mimicking microfluidic system to study Ralstonia pseudosolanacearum biofilm formation - Chu, Lan Thanh; Laxman, Deeksha; Abdelhamed, Jenna; Pirlo, Russell Kirk; Fan, Fei; Wagner, Nicholas; Tran, Tuan Minh; Bui, Loan (Frontiers in Bioengineering and Biotechnology, 2024)
The bacterial wilt pathogen Ralstonia pseudosolanacearum (Rps) colonizes plant xylem vessels and blocks the flow of xylem sap by its biofilm (comprising of bacterial cells and extracellular material), resulting in devastating wilt disease across many economically important host plants including tomatoes. The technical challenges of imaging the xylem environment, along with the use of artificial cell culture plates and media in existing in vitro systems, limit the understanding of Rps biofilm formation and its infection dynamics. In this study, we designed and built a microfluidic system that mimics the physical and chemical conditions of the tomato xylem vessels, and allowed us to dissect Rps responses to different xylem-like conditions. The system, incorporating functional surface coatings of carboxymethyl cellulosedopamine, provided a bioactive environment that significantly enhanced Rps attachment and biofilm formation in the presence of tomato xylem sap. Using computational approaches, we confirmed that Rps experienced linear increasing drag forces in xylem-mimicking channels at higher flow rates. Consistently, attachment and biofilm assays conducted in our microfluidic system revealed that both seeding time and flow rates were critical for bacterial adhesion to surface and biofilm formation inside the channels. These findings provided insights into the Rps attachment and biofilm formation processes, contributing to a better understanding of plant-pathogen interactions during wilt disease development.